Mini-review: Ferrite nanoparticles in the catalysis - Kharisov, Boris I.; Rasika Dias, H.V.; Kharissova, Oxana Vasilievna (Elsevier, 2019)
Recent applications of ferrite nanoparticles as catalysts in organic processes are reviewed. Catalytic applications include the use of mainly cobalt, nickel, copper, and zinc ferrites, as well as their mixed-metal combinations with Cr, Cd, Mn and sometimes some lanthanides. Core–shell nanostructures with silica and titania are also used without loss of magnetic properties. The ferrite nanomaterials are obtained mainly by wet-chemical sol-gel or co-precipitation methods, more rarely by the sonochemical technique, mechanical high-energy ball milling, spark plasma sintering, microwave heating or hydrothermal route. Catalytic processes with application of ferrite nanoparticles include decomposition (in particular photocatalytic), reactions of dehydrogenation, oxidation, alkylation, C–C coupling, among other processes. Ferrite nano catalysts can be easily recovered from reaction systems and reused up to several runs almost without loss of catalytic activity.